Increased Depressive and Anxiety Symptoms Predict Increased Severity of Functional Impairment After Five Years: A Nationally Representative Retrospective Cohort Study - Elisabeth C. DeMarco; Samantha Zocher; Blake Miyamoto; Leslie Hinyard; Divya S. Subramaniam (Journal of Patient-Centered Research and Reviews)
Purpose: Performing self-care and domestic life tasks are key aspects of functional independence for older adults. While both depression and anxiety symptoms are correlated with increased functional limitation, these disorders are often studied separately, despite frequent co-occurrence and plausible interaction, and without the consideration of social health. This study examined the impact of comorbid depressive and anxiety symptoms, controlling for social participation and loneliness, on severity of functional limitation in a nationally representative sample of older adults to improve patient-centered care.